Unstructured source artifacts ontology for requirement validation in GDSD - Altaf, Sohaib; Shah, Asadullah; Imtiaz, Najma; salaam Shah, Abdul; Faiz Ahmed, Syed (International Journal of Engineering and Technology, 2018)
Analyst while transformation, may not capture true representation of user opinion thus creating deviation from actual user needs. Role of stakeholder is primary in both requirement elicitation and validation process. In elicitation stage they are initiator whereas in validation stage they are authenticator of their needs. Invalid requirements if verified may not be a deviation from specified behavior but deviation from user needs. Requirement validation process ensure that requirements should be representing all primary and intermediary artifacts as well a shared opinions of their contributors. This highlights the importance of source artifacts without which requirement validation cannot assured. Researchers didn’t propose any framework for requirement validation in context of GDSD in which source artifacts grows exponentially, and stakeholders are located in diversified locations. Due to unstructured nature of source artifacts, they are not electronically indexed and versioned controlled and this makes difficulty in preserving them. Requirement validation is not possible when source artifacts are not available along with their contributors. The major contribution of this paper to address problem of requirement validation in GDSD in absence of stakeholder to make it collocating environment. This paper introduced ontological solution of requirement validation in which target artifacts are validated against source artifact using their semantic relationship. This paper proposed an unstructured source artifact based ontological model for requirement validation in GDSD environment.